Swedish - Finnish glossary: vegetables in cultivation - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with words for vegetables in cultivation. Contains approximately 50 entries. Published in Kieliviesti 2/2009. 2009.

Swedish - Finnish glossary with words for vegetables in cultivation. Contains approximately 50 words. Published in Kieliviesti 2/2009. 2009.

Svensk-sverigefinsk ordlista med ord för grönsaker i grönsakslandet. Innehåller ca 50 ord. Publicerad i Kieliviesti 2/2009. 2009.
Svensk-finsk ordlista: grönsaker i grönsakslandet
Keywords: languages; språk; vegetables; grönsaker; Vegetables; Grönsaker; vegetable cultivation; grönsaksodling; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur